DAMPAK JUDI TOGEL TERHADAP MASYARAKAT DI DESA MOTOLING DUA KECAMATAN MOTOLING KABUPATEN MINAHASA SELATAN - Rivana Noviana Rindengan; Ferdinand Kerebungu; Zoni Henki Singal (Labor Program Studi Pendidikan Sosiologi, 2020)
The purpose of this research is to find out, describe, analyze the factors that encourage people to gamble togel and the impact of lottery gambling on the community in Motoling Dua Village, Motoling District, South Minahasa Regency. This research uses qualitative methods, with data collection techniques such as observation and in-depth interviews. While the data analysis technique in this study was carried out using the interactive model of Miles & Humbermen, with several stages, namely, data reduction, data presentation, and data verification. The results of this study indicate that there are several factors that encourage people to gamble lottery in Motoling Dua Village, namely: the wrong way of thinking of the community, economic factors, social environmental factors, belief factors in dreams while sleeping which of course has an impact on lottery gambling and to the surrounding community. The positive impact of lottery gambling is to increase the standard of living. The negative impact of lottery gambling, namely, there are fights, theft occurs, people become stressed, become lazy to work. The role of religious leaders, community leaders, and the police is very important in overcoming the rampant lottery gambling in Motoling Dua Village.